The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.14202/vetworld.2015.1237-1242
|View full text |Cite
|
Sign up to set email alerts
|

A study on the prevalence of Aeromonas spp. and its enterotoxin genes in samples of well water, tap water, and bottled water

Abstract: Aim:The aim of this work was to study the prevalence of Aeromonas spp. and its enterotoxin genes in various water sources.Materials and Methods:125 samples (50 from well water, 50 from tap water, and 25 from bottled water) were collected from various sources in and around Greater Hyderabad Municipal Corporation and examined for the presence of aeromonads by both cultural and polymerase chain reaction (PCR) assay. Alkaline peptone water with ampicillin was used as enrichment. Aeromonas isolation medium and ampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Higher incidence was reported by Ibrahim et al [41] who found (60%) of beef and (58%) of mutton samples in Australia to be contaminated with this bacterium. The degree of variations in the results obtained by many authors can be due to the disparity of geographical locations, the methods and techniques adopted for isolation, samples collecting seasons [42], nutrition factors, livestock density, breeding systems, methods used in the slaughtering process, and the level of sanitation, which considered among the most important factors that affect the different levels of contamination with A. hydrophila in animal food samples [43]. The findings obtained in this study are concerning because different spp.…”
Section: Discussionmentioning
confidence: 99%
“…Higher incidence was reported by Ibrahim et al [41] who found (60%) of beef and (58%) of mutton samples in Australia to be contaminated with this bacterium. The degree of variations in the results obtained by many authors can be due to the disparity of geographical locations, the methods and techniques adopted for isolation, samples collecting seasons [42], nutrition factors, livestock density, breeding systems, methods used in the slaughtering process, and the level of sanitation, which considered among the most important factors that affect the different levels of contamination with A. hydrophila in animal food samples [43]. The findings obtained in this study are concerning because different spp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the virulence gene content of isolates from different isolation sources, including diseased humans, are similar ( Figure S7 ). Given its characteristics [ 1 , 2 ], the species has the potential to infect humans from food sources, especially fish [ 56 ], and from water used for consumption [ 57 ]. A. veronii is a mesophilic species of the genus Aeromonas [ 2 ] able to proliferate at higher temperatures, and some studies, such as the one by Yuwono et al [ 5 ], reported a higher frequency of Aeromonas infections in warmer seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Aeromonas spp. are known as opportunistic pathogens capable of causing various diseases in aquatic animals, livestock, and humans and are widely distributed in ecosystems encompassing rivers, lakes, oceans, and urban domestic water [1,2]. Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%